PENGARUH BRAND IMAGE, PRODUCT QUALITY DAN KREATIVITAS IKLAN TERHADAP KEPUTUSAN PEMBELIAN THE ORIGINOTE DI KOTA BATAM - Sherina Febriani; Hikmah Hikmah (SCIENTIA JOURNAL, 2026)
This research aims to examine the level of influence of brand image, product quality, and advertising creativity on purchasing decisions for The Originote in Batam City. This study uses a quantitative approach. The sample size was 204 respondents, namely consumers who have purchased and used The Originote products in the Sagulung area, Batam City. The research data were obtained from primary sources, then processed using SPSS software version 29. The results of the analysis show that brand image has a positive and significant effect on purchasing decisions for The Originote in Batam City. Product quality is also proven to have a positive and significant effect on purchasing decisions. In addition, advertising creativity has a positive and significant impact on these purchasing decisions. Simultaneously, brand image, product quality, and advertising creativity together have a positive and significant effect on purchasing decisions for The Originote in Batam City.